Phenotype/genotype relationships in sickle cell disease: a pilot twin study. - Weatherall, M; Higgs, D; Weiss, H; Weatherall, D; Serjeant, G (2005)
The roles of genetic and non-genetic factors in the haematology, growth and clinical features of sickle cell disease have been studied in nine identical twin pairs (six homozygous sickle cell disease, three sickle cell-haemoglobin C disease). A comparison group of 350 age-gender matched sibling pairs, selected to have an age difference of <5 years, was used for assessing the concordance of numerical data. Attained height, weight at attained height, fetal haemoglobin, total haemoglobin, mean cell volume, mean cell haemoglobin and total bilirubin levels showed significantly greater correlation in identical twins than in siblings. Twins showed similarities in the prevalence and degree of splenomegaly, susceptibility to priapism, and in onset of menarche, but other clinical complications were discordant in prevalence and severity. These findings suggest that physical growth and many haematological characteristics are subject to genetic influences, but that non-genetic factors contribute to the variance in disease manifestations.